Experimental Research of Transcritical CO2 Heat Pump System with Double Expansion Valve - Wang Zhe; Gong Yi; Wu Xuehong; Hou Feng (Zhileng xuebao, 2012)
A new transcritical CO2 heat pump systems with dual expansion valve and balance CO2 liquid reservoir adjustment device was introduced. The influence of the internal heat exchanger (IHX) on the system performances was analyzed on the basis of relative COP and compressor power. It is concluded that: the compressor power of system with IHX is relatively low when the high side pressure is over 10MPa, and the evaporating temperature is below 0℃. The COP of the system without IHX is about 3% to 5% higher than the system with IHX when the evaporating temperature is over 5℃. The new devices can control high and low side pressure effectively, and decrease the impact of pressure fluctuations on its COP. The experimental results provide important basis for the development of the transcritical CO2 heat pump systems.